Condition dependence of male and female reproductive success: insights from a simultaneous hermaphrodite. Issue 3 (18th January 2016) - Janicke, Tim; Chapuis, Elodie
Abstract: Sexually selected traits are predicted to show condition dependence by capturing the genetic quality of its bearer. In separate‐sexed organisms, this will ultimately translate into condition dependence of reproductive success of the sex that experiences sexual selection, which is typically the male. Such condition dependence of reproductive success is predicted to be higher in males than females under conditions promoting intense sexual selection. For simultaneous hermaphrodites, however, sex allocation theory predicts that individuals in poor condition channel relatively more resources into the male sex function at the expense of the female function. Thus, male reproductive success is expected to be less condition dependent than female reproductive success. We subjected individuals of the simultaneously hermaphroditic snail Physa acuta to two feeding treatments to test for condition dependence of male and female reproductive success under varying levels of male–male competition. Condition dependence was found for female, but not for male, reproductive success, meaning that selection on condition is relatively stronger through the female sex function. This effect was consistent over both male–male competition treatments. Decomposition of male and female reproductive performance revealed that individuals in poor condition copulated more in their male role, indicating an increased male allocation to mate acquisition. These findings suggest that sex‐specific condition dependence of reproductive success is at least partially driven by condition‐dependent sex allocation. We discuss the implications of condition‐dependent sex allocation for the evolution of sexually selected traits in simultaneous hermaphrodites. Abstract : We tested for sex‐specific condition dependence of reproductive success in the simultaneously hermaphroditic freshwater snail Physa acuta under conditions allowing pre‐ and postcopulatory sexual selection to operate. Our results indicate that female, but not male, reproductive success is condition dependent. We discuss our findings in the context of condition‐dependent sex allocation.